Adaptation of the point defect model to simulate oxidation kinetics of 316L stainless steel in the pressurised water reactor environment. (June 2021) - Matthews, R.P.; Knutsen, R.D.; Westraadt, J.E.; Couvant, T.
Highlights: Oxidation thickness was measured physically using focussed ion beam cross-sections. Oxidation kinetics was reduced as the temperature increased through the range of 290°C–360°C. The Point Defect Model has been adapted to predict 316 L oxidation kinetics in high temperature primary water. Departure from Arrhenius behaviour may be due to a loss of coherency at the metal oxide interface. Abstract: The kinetics of oxide growth on 316 L stainless steel was measured after exposing samples, to a typical primary water environment at three temperatures (290℃, 320℃ and 360℃) and for test durations ranging from 1 h to 7000 h. Contrary to expected Arrhenius behaviour, the oxide growth decreased as temperature increased in this range. The Point Defect Model has been adapted to accommodate this departure. It is argued that the oxide growth behaviour is linked to the degrading coherency across the metal/oxide interface and supported by grain orientation analysis that demonstrates temperature dependence for preferred oxide growth on specific grain orientations.